Association of Fat Mass and Obesity-associated Gene (FTO) rs9939609 Variant with Early Onset Obesity among Bataknese and Chinese Children in Indonesia: A Case-control Study - Siska Mayasari Lubis; Miswar Fattah; Harun Alrasyid Damanik; Jose Rizal Latief Batubara (The Prodia Education and Research Institute (PERI), 2017)
BACKGROUND: Childhood obesity is associated with the risk of adult obesity and obesity-related chronic disease. The fat mass and obesity-associated gene (FTO) rs9939609 variant are of particular interest because of its association with body mass index (BMI) and obesity-related phenotypes. This study was conducted to investigate the association between FTO gene rs9939609 variant with early onset obesity among Bataknese and Chinese children in Medan, Sumatera Utara, Indonesia.METHODS: The case-control study was carried out at 10 elementary schools in Medan. There were 212 children recruited; 56 early onset obesity and 61 control Bataknese and 49 early onset obesity and 46 control Chinese children. This study included a questionnaire, anthropometric measurements, and blood test analysis. rs9939609 polymorphism genotyping was performed using RT-PCR. Logistic regression, odds ratio (OR) and 95% confidence interval (CI) were calculated to determine the risk of obesity associated with the risk alleles, p<0.05 was considered as statistically significant.RESULTS: This study found a significant association between rs9939609 and early onset obesity in Chinese children (p=0.01), but not in Bataknese. The frequency of AA genotype was lower in the early onset obesity than in the normal weight children, while an OR of 0.69 showed that this genotype may protect against weight gaining and that the TT genotype may predispose to obesity.CONCLUSION: We concluded that the FTO gene rs9939609 is associated with early onset obesity in Chinese ethnicity but not in Bataknese.KEYWORDS: pediatric obesity, FTO gene, rs9939609, polymorphism, Indonesia